Smoking prevalence among male secondary school students in Makkah region - Al-Maimani, Ghassan; Taeyb, Mustafa; AlQahtani, Ali H.; Shata, Mustafa; AlQahtani, Saleh M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Many previous researches have been conducted in different regions of Saudi Arabia to identify the prevalence of smoking among the intermediate, secondary and high school but no studies have been conducted at Makka region.This study aimed to calculate smoking prevalence among the male secondary school students in Makka region and try to explore its causes. Methods:This cross sectional study was conducted at three male secondary schools in Makka region selected randomly. The age of the students was ranged from 15 to 18 years. Data was collected by an Arabic questionnaire and was analysed by using the statistical package of social science (SPSS) version 16. Results: It was found that 20.2% (83 students out of 411) were smokers, 77.1% of them were Saudis. Cigarette smoking was found to be the commonest type (44%) of smoking among them. About 20% of the smokers reported that they started smoking because they have smoker friends, while about 19% reported that they started smoking because they have one or two smokers in their family and about 10% reported they began smoking as they were seeing it as one sign of manhood. Unfortunately, only 65.1% of the smoker students attempted to quit smoking. Conclusions:Despite the apparent awareness of the general public regarding the hazardous effects of smoking, the prevalence of smoking in Makkah secondary school students is relatively high. Extensive health education and religious orientation program is urgently needed to combat the expected future epidemic of smoking.